(untitled) (Tạp chí Y học Cộng đồng, 2024)
Objective: To assess the general knowledge of nutrition of guardians when taking their children to get vaccinated at the Vaccination Room, National Hospital For Tropical Diseases in 2023 Method: Cross-sectional study of 99 guardians when taking their children to get vaccinated at the National Hospital For Tropical Diseases in 2023-2024. Results: Female guardians accounted for 74.7%. The proportion of guardians with children over 24 months old was 33.3%. The proportion of guardians with low knowledge of nutritional group classification (41.4%). 66.7% of guardians knew which substances provide energy, foods belonging to the animal protein group (88.9%). Over 75% of guardians know about the classification of nutrient groups and the foods that provide nutrients for each group, so 99% of guardians are aware of the need to eat enough food from the groups and 96% of guardians understand that nutrition affects children’s development. When surveying more deeply the group of guardians of children over 24 months old, 15.2% of guardians have correct knowledge about the oil/fat needs of children 2-5 years old, while the percentage of guardians who answered that they do not know is 75.8%. Regarding the nutritional needs of children 6-8 years old, the percentage of guardians who answered correctly was only 33.3%; the majority answered incorrectly (51.5%). 54.5% of guardians agree that children with diarrhea still need to use oil/fat. Conclusion: General knowledge of nutrition of guardians when taking children to get vaccinated at the Vaccination Room, National Hospital For Tropical Diseases in 2023 is still low. More guardians need to conduct further research on general practical knowledge of guardians when taking children to get vaccinated to serve as a basis for nutritional counseling, contributing to reducing the rate of malnutrition in children.